2022
DOI: 10.1002/acr.24767
|View full text |Cite
|
Sign up to set email alerts
|

Slow Colonic Transit in Systemic Sclerosis: An Objective Assessment of Risk Factors and Clinical Phenotype

Abstract: Objective. Up to 50% of patients with systemic sclerosis (SSc) experience slow colonic transit, which may be associated with severe outcomes. Our objective, therefore, was to identify specific clinical features associated with slow colonic transit in SSc.Methods. SSc patients with gastrointestinal symptoms were prospectively enrolled and completed a scintigraphy-based whole gut transit study. Clinical features were compared between patients with and without slow colonic transit in univariate and multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This prevalence is similar to the findings of a study by Suliman et al in which antivinculin antibodies were identified in 37% of a SSc cohort enriched for GI disease and in 32% of an SSc cohort enriched for vascular disease (15). While our cohort had slightly more severe GI disease compared to patients who did not complete the WGT study (25), we also included patients who were minimally symptomatic, which could explain why the prevalence of antivinculin antibodies in our cohort was slightly lower.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is similar to the findings of a study by Suliman et al in which antivinculin antibodies were identified in 37% of a SSc cohort enriched for GI disease and in 32% of an SSc cohort enriched for vascular disease (15). While our cohort had slightly more severe GI disease compared to patients who did not complete the WGT study (25), we also included patients who were minimally symptomatic, which could explain why the prevalence of antivinculin antibodies in our cohort was slightly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of neuropathic and myopathic processes contributes to delayed colonic transit leading to symptoms such as distension or fullness after meals, abdominal pain and straining during bowel movements [69]. Risk factors for delayed colonic transit include female sex, presence of telangiectasia, presence of anticentromere antibodies, past history of smoking and a Medsger gastrointestinal severity score of at least 3 [9 ▪ ]. After constipation, diarrhoea is the second most common clinical feature of large intestine involvement in SSc.…”
Section: Upper Gastrointestinal Tract Involvementmentioning
confidence: 99%
“…As significant clinical heterogeneity exists in SSc-GI disease [6,9 ▪ ,10,11], the underlying pathophysiology is complex and may vary across patient subsets. The classic hypothesis proposed by Sjogren nearly 3 decades ago suggested that SSc-GI disease arises from a three-step sequential process, which includes neural dysfunction, smooth muscle atrophy and fibrosis [12].…”
Section: Pathophysiologymentioning
confidence: 99%